PENGARUH AUTHENTIC PROBLEM BASED LEARNING (aPBL) TERHADAP PENGUASAAN KONSEP IPA SISWA KELAS IV SEKOLAH DASAR - Marlina Marlina; Sugeng Utaya; Lia Yuliati (Graduate School of Universitas Negeri Malang, 2017)
This study aims to describe the effect of Authentic Problem Based Learning (aPBL) on the mastery of the concept of science class IV students of primary school. This type of research is an experimental quasi with posttest only control group design. The sample consisted of 63 students divided into experimental class and control class. The sample selection technique used purposive sampling. The data of this research are analyzed quantitatively using t test and effect size. The results of this study indicate that aPBL influence on the mastery of the concept of science class IV students of primary school of 0.807. The average mastery of science concepts of students who studied with aPBL of 70.31 while the mastery of science concepts of students who learn with conventional learning of 60.16. This shows that aPBL affect the mastery of the concept of science IPA class IV students of primary school.Penelitian ini bertujuan untuk mendeskripsikan pengaruh Authentic Problem Based Learning (aPBL) terhadap penguasaan konsep IPA siswa kelas IV Sekolah Dasar. Jenis penelitian merupakan penelitian quasi experimental dengan posttest only control group design. Sampel penelitian terdiri atas 63 siswa yang terbagi dalam kelas eksperimen dan kelas kontrol. Teknik pemilihan sampel menggunakan purposive Sampling. Data penelitian ini dianalisis secara kuantitatif menggunakan uji t dan effect size. Hasil penelitian ini menunjukkan bahwa aPBL berpengaruh terhadap penguasaan konsep IPA siswa kelas IV Sekolah Dasar sebesar 0,807. Rata-rata penguasaan konsep IPA siswa yang belajar dengan aPBL sebesar 70,31, sedangkan penguasaan konsep IPA siswa yang belajar dengan pembelajaran konvensional sebesar 60,16. Hal ini menunjukkan bahwa aPBL berpengaruh terhadap penguasaan konsep IPA siswa kelas IV Sekolah Dasar.